2002
DOI: 10.1074/jbc.m112274200
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin Causes G1 Arrest of Endothelial Cells through Inhibition of Cyclin D1

Abstract: Endostatin, a type XVIII collagen fragment, is a potent antiangiogenic molecule that inhibits endothelial cell migration, promotes apoptosis, and induces cell cycle arrest in vitro. We have investigated the mechanism by which endostatin causes G 1 arrest in endothelial cells. Endostatin decreased the hyperphosphorylated retinoblastoma gene product and down-regulated cyclin D1 mRNA and protein. Importantly, endostatin was unable to arrest cyclin D1 overexpressing endothelial cells, suggesting that cyclin D1 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
116
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(121 citation statements)
references
References 25 publications
4
116
0
1
Order By: Relevance
“…Consistent with the present results, earlier studies show that various anti-angiogenic molecules, such as endostatin, capsaicin and curcumin, inhibit Rb phosphorylation and DNA synthesis of endothelial cells through downregulation of cyclin D1. 40,41 On the contrary, treatment of emodin in bovine aortic endothelial cells induced G2/M phase arrest of cell cycle. 38 Our experiment also showed G2/M phase arrest by emodin in HUVECs; however, its concentration was higher enough for inducing cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the present results, earlier studies show that various anti-angiogenic molecules, such as endostatin, capsaicin and curcumin, inhibit Rb phosphorylation and DNA synthesis of endothelial cells through downregulation of cyclin D1. 40,41 On the contrary, treatment of emodin in bovine aortic endothelial cells induced G2/M phase arrest of cell cycle. 38 Our experiment also showed G2/M phase arrest by emodin in HUVECs; however, its concentration was higher enough for inducing cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that endostatin blocked the VEGF-mediated signaling pathway, inhibited the proliferation of endothelial cells, and promoted the apoptosis of endothelial cells. Hanai et al (4) found that endostatin decreased the activity of β-catenin, inhibited cyclin D1 expression and induced G1 arrest of endothelial cells. MacDonald et al (5) also reported that endostatin could remodel the blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…9 Cell surface glypicans have also been shown to be low-affinity endostatin receptors. 10 Endostatin has been implicated in several signaling pathways, such as downregulation of c-myc, 11 RhoA activity 12 and cyclin-D1, 13 blockage of VEGF signaling, 14,15 and inhibition of the wnt-signaling pathway. 16 Furthermore, endostatin has been shown to bind and inactivate metalloproteinases [17][18][19] and to regulate a spectrum of genes that suppress angiogenesis.…”
Section: Introductionmentioning
confidence: 99%